Assessment of Doctor-Patient Communication Among Residents in Internal Medicine Polyclinic At RSUP Dr. Mohammad Hoesin Palembang 2014 Using Simplified Checklist of Calgary Cambridge Guide - Awinda, Dipika; Syakurah, Rizma; Fadilah, Mariatul (Fakultas Kedokteran Universitas Pelita Harapan, 2019)
Introduction : Misperceptions between doctors and patients can bring negative impact for both the doctors and patients. Misperceptions may occur due to miscommunication during doctor-patient communication. Therefore, assessment during the communication process is necessary.Methods : This study was a descpritive study with qualitative approach. Checklist Calgary Cambridge Guide (CCCG) was chosen as instrument because it has been widely used in many country.The study was condicted in Polyclinic Internal Medicine of dr. Mohammad Hoesin Hospital due to its high patient load with various diseases that is suitable for doctor-patient communication observation. Subjects were six residents in the department. Observation was done during the communication process. Deep interview was then done to assess the resident’s knowledge and opinions in doctor-patient communication and barriers related to it. Results : Majority of the residents failed to do some points of the CCCG, which includes self introduction, role and nature of interview, obtain consent and explain process, obtain permission prior to physical examination.Conclusions : In conclusion, the doctor-patient communication among residents in Internal Medicine Polyclinic At RSUP Dr. Mohammad Hoesin Palembang.